A Word Spoken at the Right Time: A Hermeneutic Analysis of Proverbs 25:11 - Anggelo, Immanuel Raphael; Haryanti, Ninik (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
One of the critical points in communication is choosing appropriate diction and words that suit the situation. If it is inappropriate and conveyed out of context, miscommunication can trigger arguments or misunderstandings. The root of the problem is using inappropriate sentences when verbal communication occurs. Among several Bible verses that provide advice about good words, this research will formulate the meaning in the Book of Proverbs 25:11 regarding the concept of timely words in communication. With this study, it is hoped that conceptual indicators will emerge as to what the Bible means by these good words. The approach used in extracting the text is the exegesis of the verse Proverbs 25:11. Based on research, it can be concluded that good speech, apart from being a communication skill, is also formed by the presence of wisdom in the communicant and communicator. This is a sign that someone has spiritual maturity, visible credibility, and integrity in relationships with fellow humans. It was also concluded that to suppress bad habits in speaking, good education and correct understanding of the truth of God's word is needed on the one hand, and awareness that every word that comes out of the mouth cannot be revoked and has consequences, on the other hand.